Integrating piezoresistive sensors on the embouchure analysis of the lower lip in single reed instrumentalists: implementation of the lip pressure appliance (LPA) - Miguel Pais Clemente; Joaquim Mendes; Joana Cerqueira; André Moreira; Mário Vasconcelos; Afonso Pinhão Ferreira; José Manuel Amarante (Wiley, 2019)
Abstract Background It is essential to understand, characterize, and measure the embouchure mechanism of a wind instrumentalists, where the applied forces on the perioral tissues can usually promote discomfort or pain. Methods The sample consisted of five clarinet players and five saxophone players. The embouchure force measurements at the lower lip area were assessed using a piezoresistive sensor (FlexiForceTM, Tekscan, Boston, USA, 0.07 kgf/cm2) placed on the lower part of the mouthpiece of the single reed instrument. Furthermore, each participant performed three times three different notes at different pitches: high, medium, and low. An intraoral device was manufactured in order to dissipate the existing pressures. Results The piezoresistive sensors applied to the mouthpiece of the five clarinetists presented values between 16 and 226 g of force. In the case of the five saxophonists, the values registered were between 5 and 320 g of force. Conclusions Piezoresistive sensors are a valid option to characterize that single reed instrumentalists apply substantial forces at the lower lip that can be equivalent to medium orthodontic forces. The implementation of the Lip Pressure Appliance can be a valid solution on the prevention of eventual lesions resulting from the embouchure forces.